2020
DOI: 10.1016/j.ijid.2020.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clostridioides difficile infection on the outcome of patients receiving a hematopoietic stem cell transplantation

Abstract: Objectives: Clostridioides difficile infections (CDI) are common in autologous (auto-HSCT) or allogenic hematopoietic stem cell transplant (allo-HSCT) recipients. However, the impact of CDI on patient outcomes is controversial. We conducted this study to examine the impact of CDI on patient outcomes. Methods: We performed a retrospective single-center study, including 191 lymphoma patients receiving an auto-HSCT and 276 acute myeloid leukemia (AML) patients receiving an allo-HSCT. The primary endpoint was over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(75 reference statements)
0
4
1
Order By: Relevance
“…Of note, all 10 patients were receiving empirical broad-spectrum antibiotic treatment, and none developed severe CDI. Compared with previous reports [9], both the CDI incidence (13%) and recurrence (2%) were low.…”
Section: Discussioncontrasting
confidence: 86%
“…Of note, all 10 patients were receiving empirical broad-spectrum antibiotic treatment, and none developed severe CDI. Compared with previous reports [9], both the CDI incidence (13%) and recurrence (2%) were low.…”
Section: Discussioncontrasting
confidence: 86%
“…Most studies involving cancer patients have reported low rates of severe or fatal cases of CDI [12,29 ▪▪ ,41,42]. For instance, a recent study in patients with acute myeloid leukaemia (AML) found no differences in various clinical parameters, such as length of stay, need for ICU admission, development of acute renal failure, chemotherapy response, or mortality, between patients with or without CDI [11 ▪ ].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Different studies, using nonhomogenous definitions, have reported CDI incidence and infection rates ranging from 6% to 33% in cancer patients [6,8–10,11 ▪ ,12], with higher rates in those with haematological malignancies compared to those with solid tumours [13]. Specifically in hematopoietic stem cell transplant (HSCT) recipients, CDI incidences have ranged from 8% to 31% depending on the source and type of transplant, with umbilical cord and allogeneic HSCT showing the highest incidences [8,14–17].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Weber et al 27 performed a retrospective study evaluating the impact of CDI on HCT recipients. They included 276 patients receiving allo-HCT and 191 patients receiving auto-HCT.…”
Section: Adultsmentioning
confidence: 99%